Effect of ruthenium oxide on the capacitance and gas‐sensing performances of cobalt oxide @nitrogen‐doped graphene oxide composites. (17th July 2021) - Ramesh, Sivalingam; Lee, Young‐Jun; Shin, Kyeongho; Sanjeeb, Lama; Karuppasamy, K.; Vikraman, Dhanasekaran; Kathalingam, Adaikalam; Kim, Hyun‐Seok; Kim, Heung Soo; Kim, Joo‐Hyung
Summary: Co3 O4 /RuO2 @nitrogen‐doped graphene oxide (NGO) composite materials were synthesized through a sonication‐assisted thermal reduction method in the presence of cobalt and ruthenium starting reagents for supercapacitor and gas sensor applications. The composite materials were characterized using various analytical tools to confirm the structural and morphological properties. The synthesized Co3 O4 /RuO2 @NGO composites showed the nanostructured grains anchored on the NGO surface. The electrochemical storage performance was studied by using cyclic voltammetry, galvanostatic charge discharge, and electrochemical impedance spectroscopy using a two‐electrode asymmetric configuration. The prepared Co3 O4 /RuO2 @NGO electrode exhibited a maximum capacitance of ~149 F/g at an applied current of ~0.5 A/g, an energy density of 20.69 Wh kg −1, and at a power density of 250 W kg −1 . The cycling behavior of the fabricated asymmetric capacitor revealed a 90% capacitance retention after 5000 cycles. Moreover, the prepared composite material was used successfully for dimethyl methylophosphonate (DMMP) vapor detection, showing excellent sensitivity, selectivity, and stability. Therefore, the constructed Co3 O4 /RuO2 @NGO composite is a suitable material for supercapacitors and DMMP gas‐detection applications. Abstract : Co3 O4 /RuO2 @nitrogen doped graphene oxide (NGO) composite materials were synthesized through a sonication assisted thermal reduction method. From the supercapacitive and gas sensing performance tests, the novel composite shows the feasibility for supercapacitors and DMMP gas detection applications.